Potter Syndrome and Congenital Heart Disease: Potter Syndrome and Congenital Heart Disease - Mehralizadeh, Semira; Nooripoor, Shamsollah (Journal of Pediatric Nephrology, 2023)
Potter syndrome is a lethal congenital anomaly resulting from oligohydramnios due to renal agenesis and dysfunction. Because neonates with Potter syndrome have pulmonary hypoplasia, it is incompatible with life and the neonates will expire with respiratory distress during the first hours of life. Potter syndrome is rarely accompanied by congenital heart disease. We report a case of severe Potter syndrome with pulmonary valve atresia that expired a few hours after birth.